Role and expression of cry1 in the adductor muscle of the oyster Crassostrea gigas during daily and tidal valve activity rhythms. (13th September 2016) - Mat, Audrey M.; Perrigault, Mickael; Massabuau, Jean-Charles; Tran, Damien
ABSTRACT: Cryptochromes are flavin- and pterin-containing photoreceptors of the cryptochrome/photolyase family. They play critical roles in organisms, among are which light-dependent and light-independent roles in biological rhythms. The present work aimed at describing a cryptochrome gene in the oyster Crassostrea gigas by (i) a characterization and phylogenetic analysis and (ii) by studying its expression in the relationship to rhythmic valve behavior in different entrainment regimes. Cryptochrome expression was focused on the adductor muscle of the oyster, the effector of the valve behavior. The results suggest involvement of Cgcry1 in oyster rhythmicity as a sensor of environmental zeitgebers, associated with circadian rhythms and potentially to tidal activity. The characterized gene belongs to type 1 cryptochrome/insect-type cry. Additionally, Cgcry1 presented a daily oscillation under L:D entrainment, which disappeared in constant darkness. Transcript expression of Cgcry1 also oscillated at tidal frequency under tidal entrainment and in constant darkness. Finally, exposure of tidally entrained oysters to saxitoxin (STX)-producing alga Alexandrium minutum induced a dose effect response in oysters by first altering Cgcry1 expression and then the behavior of oysters with increasing concentrations of toxins. This study initiates the characterization of the molecular clock in the oyster C. gigas and its interactions with environmental zeitgebers.